Student-centered learning in the digital age: in-class adaptive instruction and best practices - Daniel Ginting; Delli Sabudu; Yusawinur Barella; Ahmad Madkur; Ross Woods; Mezia Kemala Sari (Institute of Advanced Engineering and Science, 2024)
Adaptive instruction is a promising solution to the limitations of traditional classroom instruction, which assumes that all students learn in the same way and at the same pace. Adaptive instruction tailors the learning experience to each student’s needs and abilities. Several adaptive instruction tools and platforms exist, including intelligent tutoring systems, learning management systems, mobile apps, AI chatbots, and adaptive machine-learning programs. The Adaptive Instruction of Student Control Theoretical Framework suggests that allowing students to control their use of learning resources leads to better learning outcomes. Implementing adaptive instruction in higher education can be difficult due to faculty buy-in, technical infrastructure, and student motivation. Effective instructional design is crucial for adaptive instruction to support student control and maximize benefits. Overall, instructors must pay attention to student motivation and work to create learning environments that foster motivation, autonomy, and engagement to implement adaptive instruction successfully.